Contributi allo studio della ≪reticentia≫ - Longo, Giovanna (Euphrosyne, 1993)
Abstract Study was carried out on cases of reticentia using categories offered by studies concerning this figure of speech. This made possible to analize and to identify as cases of reticentia two passages, the former taken from Amphitruo by Plautus (v. 741), the latter from an epistle to Atticus by Cicero (7,23,2).